An integrated framework for supporting fuzzy decision-making in networked manufacturing environments - Vieira, Gaspar Gonçalves (2015)
In this paper we propose an integrated framework, based on smart objects to support fuzzy decision-making processes applied to manufacturing environments. The processes involved range from factory-production level up to higher decision-making levels, either in the context of traditional single enterprises, up to the one of supply chains and distributed and ubiquitous manufacturing environments. Therefore, the proposed framework promotes contributions for solving different kind of problems, including, among others: networked supply chain management; production planning and control; factory supervision and productivity management; real-time monitoring; data acquisition and processing. The web access via different middleware devices and tools at different process levels, along with the use of integrated algorithms and smart objects, which is possible and will promote an optimized use of knowledge and resources for supporting better decision-making. Moreover, the proposed framework also aims at promoting a wider collaboration process among various groups of stakeholders.